We shall not fail values in the national leadership of Seretse Khama, Nelson Mandela, and Julius Nyerere - Mungazi. Dickson A. (Trenton Africa World Press, 2005)
This Book focuses on pertinent political and social issues in Botswana, South Africa, and Tanzania during the leadership of Seretse Khama, Nelson Mandela, and Julius Nyerere respectively. It is a critical analysis of the nature of good and effective national leadership in these three nations based upon the values that the leaders embraced to serve their respective countries. Drawing implications for other countries of the region, the author demonstrates what he considers to be good national leadership by providing insights into the political careers of Seretse Khama of Botswana, Nelson Mandela of South Afirca, and Julius Nyerere of Tanzania. The values that these three national leaders shared in common and which made them succesful include integrity, loyalty to principle, honesty,respect to democracy, confidence in tha ability of the peole to make viable contribution to national policy and programs
Includes bibliographical references and index.
Keywords: Political Leadership-Africa, Social Values-Africa Politics and Government-South Africa Khama Seretse Mandela Nelson